Fourth-Generation Minimally Invasive Hallux Valgus Surgery With Metaphyseal Extra-Articular Transverse and Akin Osteotomy (META): 12 Month Clinical and Radiologic Results. (March 2023) - Lewis, Thomas L.; Lau, Benjamin; Alkhalfan, Yousif; Trowbridge, Samuel; Gordon, David; Vernois, Joel; Lam, Peter; Ray, Robbie
Background: Fourth-generation minimally invasive surgery (MIS) includes the multiplanar rotational deformity correction achieved through manipulation of an extra-articular distal first metatarsal osteotomy that is held with rigid fixation using 2 fully threaded screws, of which one must be bicortical to provide rotational and biomechanical stability. The aim of this study is to report the clinical and radiologic outcomes of an evolved fourth-generation MIS hallux valgus technique. Methods: A prospective single-surgeon series of consecutive patients undergoing fourth-generation MIS was performed using a distal transverse osteotomy with a minimum 12-month follow-up. The primary outcome was the Manchester-Oxford Foot Questionnaire (MOXFQ), a validated clinical patient-reported outcome measure (PROM). Secondary outcomes included radiographic deformity correction, clinical assessment, and EuroQol-5D-5L PROMs. Results: Between September 2019 and June 2021, 50 feet underwent fourth-generation MIS. The mean age was 55.8±15.3 years with a mean follow-up of 1.4 years. Preoperative and minimum 12-month primary outcome data were available for 100% of feet. There was a significant improvement in all MOXFQ domain scores, with the index domain improving from 53.4 to 13.1 ( P < .001). There was a significant improvement ( P < .001) in hallux valgus angle (32.7 to 7.9 degrees), intermetatarsal angle (14.0 to 4.2 degrees) and distal metatarsal articular angle (18.5 to 5.6 degrees). There was a significant improvement in general health-related quality of life EQ-5D-5L index and EQ-VAS scores ( P < .05). Conclusion: The fourth-generation MIS technique is a safe and effective approach to hallux valgus deformity correction with significant improvement in clinical and radiographic outcomes. Level of Evidence: Level IV, prospective case series.